III-Nitride Semiconductors based Optical Power Splitter Device Design for underwater Application - Retno Wigajatri Purnamaningsih; Nyi Raden Poespawati; Elhadj Dogheche (International Journal of Electrical and Computer Engineering (IJECE), 2018)
In this paper, we introduce III-nitrides based 1× 4 optical power splitter for underwater optical communication applications. To the best of our knowledge, this is a first study for the design of multimode interference (MMI) and four-branch taper waveguide based on GaN/sapphire. The microstructure of GaN semiconductor grown by Metalorganic Chemical Vapor Deposition (MOCVD) on (0001) sapphire reported. The numerical experimental is conducted using the 3D FD-BPM method. The results showed that the optical power splitter has an excess loss of 0.013 dB and imbalance of 0.17 dB. The results open the opportunity for the future device using this technology for the underwater application.